2014
DOI: 10.3109/02652048.2014.940008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dika wax-soybean oil-based artesunate-loaded lipospheres:in vitro–in vivocorrelation studies

Abstract: Artesunate-loaded lipospheres could be used orally or parenterally once daily, for the treatment of malaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Therefore, multidisciplinary efforts are necessary to precisely evaluate the efficacy, bioavailability, and pharmacokinetics of these multipurpose systems, considering that there is a lack of animal models for testing different DDS for specific applications [144]. In general, we observed advantages of such hybrid systems over their respective traditional DDS, which significantly improved the in vivo pharmacokinetics and the activity of several classes of drugs [67,72,100,104,118,119,128]. As in the case of protein nanoparticles, where polymer-protein conjugates for gene delivery provided biofunctionality to the systems [57], other formulations reduced in vivo tumor growth [56]; and the anti-inflammatory activity five times higher than the traditional protein nanoparticle was noticed [58].…”
Section: In Vivo Performance Of Biohybrid Polymer-based Hybrid Ddsmentioning
confidence: 76%
See 2 more Smart Citations
“…Therefore, multidisciplinary efforts are necessary to precisely evaluate the efficacy, bioavailability, and pharmacokinetics of these multipurpose systems, considering that there is a lack of animal models for testing different DDS for specific applications [144]. In general, we observed advantages of such hybrid systems over their respective traditional DDS, which significantly improved the in vivo pharmacokinetics and the activity of several classes of drugs [67,72,100,104,118,119,128]. As in the case of protein nanoparticles, where polymer-protein conjugates for gene delivery provided biofunctionality to the systems [57], other formulations reduced in vivo tumor growth [56]; and the anti-inflammatory activity five times higher than the traditional protein nanoparticle was noticed [58].…”
Section: In Vivo Performance Of Biohybrid Polymer-based Hybrid Ddsmentioning
confidence: 76%
“…A promising hybridbased lipid nanocapsule was described for the treatment of lung cancer, which described the in vivo (mice) tumor regression profile [110]. In vivo pharmacokinetics studies in rats demonstrated higher bioavailability of hybrid artesunateloaded lipospheres when compared to the commercial tablet for malaria treatment [104]. Different in vivo studies were described for SLN-and NLC-based hybrid systems for topical and parenteral applications, using mice, rat, and rabbit, as well as in human clinical trial, which demonstrated the effectiveness, nontoxicity, and bioavailability of these biodevices compared to their respective traditional DDS or free drug [86,88,94,96].…”
Section: In Vivo Performance Of Biohybrid Polymer-based Hybrid Ddsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinaeke et al examined the in vitro-in vivo correlation of wax-soybean oil-based artesunate-loaded lipospheres. It was revealed that the formulated lipospheres had maximum encapsulation efficiency of 80%, with a bioavailability enhancement factor of 2.108 when compared with tablets [151]. These studies show the potential of improved efficacy if phytochemicals are formulated as nanolipid systems.…”
Section: Lipid Nanoparticlesmentioning
confidence: 74%
“…These microcapsule matrices protect the loaded labile substances against degradation and can defend the GIT mucosa from severe irritations of various drugs as well as conceivably offer sustained drug discharge and drug targeting [10]. Many research works on Artemether loaded microcapsules has been formulated and assessed for in vivo performance in malariogenic mice [11,12].…”
Section: Introductionmentioning
confidence: 99%